2017
DOI: 10.1108/amhid-06-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of psychotropic medication to manage challenging behaviour in adults with intellectual disability: views of family members

Abstract: Purpose The purpose of this paper is to produce the views of parents and siblings of adults with intellectual or developmental disability (ID/DD) around the use of psychotropic medication to manage challenging behaviour (CB) where there is no co-existing mental illness. Design/methodology/approach Seven family members of six adults with ID/DD were interviewed using semi-structured interviews, over the telephone or face-to-face. The interviews were transcribed, coded and thematically analysed. Findings This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…This study is unique in providing a multistakeholder analysis of accounts of the use of psychotropic medications in people with ID. It extends the existing qualitative literature in this field which has typically focused solely on antipsychotic drugs28 or medication used for behaviour that challenges 29 54 55. Synthesising the results of interviews with patients, family carers and paid carers allowed us to develop broad, over-arching themes, and helps us to understand the interactions and dynamics involved in the complex process of medication decision-making.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This study is unique in providing a multistakeholder analysis of accounts of the use of psychotropic medications in people with ID. It extends the existing qualitative literature in this field which has typically focused solely on antipsychotic drugs28 or medication used for behaviour that challenges 29 54 55. Synthesising the results of interviews with patients, family carers and paid carers allowed us to develop broad, over-arching themes, and helps us to understand the interactions and dynamics involved in the complex process of medication decision-making.…”
Section: Discussionmentioning
confidence: 85%
“…However, evidence indicates that people with ID may not routinely be placed at the centre of healthcare decisions24 and carers of people with ID have reported that their views are not heard or that they are insufficiently involved by services 25 26. The literature relating specifically to psychotropic medication in people with ID is less developed, though a small body of evidence shows that both people with ID and their carers often lack knowledge about psychotropic medication and experience few opportunities for involvement in medication decision-making 27–30. It remains unclear how, and to what extent, the principles of SDM are applied in psychotropic medication decisions in contemporary UK settings.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate diagnoses can serve as a stepping-stone for accessing treatment; however, adults with ID face barriers in accessing high-quality mental health services (Edwards et al, 2017). While evidence suggests that psychotherapy can serve as effective treatment for individuals with ID (Prout & Nowak-Drabik, 2003), barriers to obtaining service for those with ID include providers’ lack of training, resources, and knowledge to serve individuals with ID (Whittle et al, 2018).…”
Section: Intellectual Disability Mental Health and Psychotherapymentioning
confidence: 99%
“…This is reflected in the high prevalence estimates of psychiatric diagnoses in adults with ID, which range from 30-50% (Cooper et al, 2007; Summers et al, 2017). While evidence suggests that psychotherapy can serve as effective treatment for individuals with ID (Prout & Nowak-Drabik, 2003), significant barriers persist for adults with ID attempting to obtain mental health services (Edwards et al, 2017). It is clear that more professional resources and training are necessary to address this unmet need.…”
mentioning
confidence: 99%
“…D'autres encore parlent de mesure de contrôle à partir du moment où la médication est administrée en réaction à un comportement en dehors de toute indication strictement thérapeutique. Ainsi, l'utilisation de la médication qui ne viserait pas à agir directement sur une condition psychiatrique serait considérée comme une mesure de contrôle (44). D'autres auteurs, au contraire, considèrent plutôt que toute forme d'utilisation de la médicationsuite à une évaluation ou non, liée directement à un diagnostic ou nonest un traitement (45).…”
Section: L'utilisation De La Médication En Psychiatrie : Thérapie Ou unclassified